Nontuberculous Mycobacteria Isolates in Respiratory Samples and Mycobacterial Pulmonary Disease in an Area of Northern Spain - Ugedo, Javier; Tabernero, Eva; Altube, Lander; Leal, María Victoria; García, Julia Amaranta (Open respiratory archives, 2024)
[Display omitted] The epidemiology of nontuberculous mycobacteria (NTM) is not well known. In this study, we aimed to determine the incidence of NTM isolates and nontuberculous mycobacterial pulmonary disease (NTM-PD) in five closely located hospitals in an area of northern Spain and analyse differences between them. Demographic, microbiological, clinical and radiological data were collected retrospectively from all patients with a NTM isolated from respiratory specimens at five hospitals between 2012 and 2019. Mycobacterium gordonae isolates were excluded. Once the data was collected, it was determined which patients met the NMT-PD criteria. 594 patients were included in the study. The mean incidence rate of NTM isolates across all five hospitals in the period studied was 4.15 per 100,000 person-year, while the rate of NTM-PD was 1.2. The annual number of isolates showed an upward trend over this period, but the same did not occur in the number of cases of NTM-PD. The species most frequently isolated were Mycobacterium avium complex (MAC) and Mycobacterium xenopi and those most frequently causing disease were MAC and Mycobacterium kansassi. There were significant differences between the five centres. Our results are in line with similar studies in Europe in terms of NTM isolation and NTM-PD incidence and species isolated; however, we do not see the upward trend in NTM-PD rates described elsewhere. The great variability in isolation and disease rates, as well as in species isolated in geographically close areas, underlines, in our opinion, the importance of local environmental factors. La epidemiología de las micobacterias no tuberculosas (MNT) no se conoce bien. Nuestro objetivo fue determinar la incidencia de aislamientos de MNT y de enfermedad pulmonar por micobacterias no tuberculosas (EP-MNT) en cinco hospitales del norte de España, próximos entre sí, y analizar las diferencias entre ellos. Se recopilaron retrospectivamente datos demográficos, microbiológicos, clínicos y radiológicos de todos los pacientes con una MNT aislada en muestra respiratoria entre 2012 y 2019 en los cinco hospitales. Se excluyeron los aislamientos de Mycobacterium gordonae. Una vez recogidos los datos, se determinó qué casos cumplían los criterios de EP-MNT. Se incluyeron 594 pacientes. La tasa de incidencia media de aislamientos de NTM en los cinco hospitales fue de 4,15 por 100.000 personas-año y la tasa de EP-MNT fue de 1,2. El número anual de aislamientos mostró una tendencia creciente durante este periodo, pero no así el de EP-MNT. Las especies aisladas con mayor frecuencia fueron Mycobacterium avium complex (MAC) y Mycobacterium xenopi y las que causaron enfermedad con mayor frecuencia fueron MAC y Mycobacterium kansasii. Hubo diferencias significativas entre los cinco centros. Nuestros resultados están en línea con estudios similares en Europa en términos de aislamiento de MNT, incidencia de EP-MNT y especies aisladas; sin embargo, no vemos la tendencia ascendente en las tasas de EP-MNT descrita en otros lugares. La gran variabilidad entre los cinco hospitales en las tasas de aislamiento y de enfermedad y en las especies aisladas resalta la importancia de los factores ambientales locales.